Natural infection of Delta mutant of SARS‐CoV‐2 in Asiatic lions of India. Issue 5 (26th August 2021) - Karikalan, M.; Chander, V.; Mahajan, S.; Deol, P.; Agrawal, R. K.; Nandi, S.; Rai, S. K.; Mathur, A.; Pawde, A.; Singh, K. P.; Sharma, G. K.
Abstract: The current pandemic caused by a novel coronavirus (SARS‐CoV‐2) has underlined the importance of emerging diseases of zoonotic importance. Along with human beings, several species of wild and pet animals have been demonstrated to be infected by SARS‐CoV‐2, both naturally and experimentally. In addition, with constant emergence of new variants, the species susceptibility might further change which warrants intensified screening efforts. India is a vast and second most populated country, with a habitat of a very diverse range of animal species. In this study we place on record of SARS‐CoV‐2 infections in three captive Asiatic lions. Detailed genomic characterization revealed involvement of Delta mutant (Pango lineage B.1.617.2) of SARS‐CoV‐2 at two different locations. Interestingly, no other feline species enclosed in the zoo/park were found infected. The epidemiological and molecular analysis will contribute to the understanding of the emerging mutants of SARS‐CoV‐2 in wild and domestic animals.